Joseph and his Magnificent Coat of many Colors - Williams, Marcia (London Walker Books, 1990)
Uses artefacts, original photographs and documentary evidence to describe what classroom life was like for children in Victorian times, what they learned, methods of teaching and control. Suggested level: primary, intermediate.
Include Colour Illustrations
Keywords: Joseph (Son of Jacob) -- Bible stories, English--Genesis -- Bible stories, English--Old Testament